How to Operate Beckert's (2010) Concept of The Power of Social Forces - Willy Hidayat (SOSIETAS, 2021)
This paper reviews the concept of Beckert's Social Grid (2010) which emphasizes that the source of market field dynamics comes from the interrelation of the three strengths of the structure. Using the concept of field, is a social arena where structures are formed, changed, and in later reproduction Beckert explained that the interrelationship between the three types of social structures as a source of market field dynamics. This paper provides a way of operationalizing the concept of Beckert 2010 that can be used in analyzing a dynamic that occurs based on the concept of Beckert's social grid that focuses on actors who harness the power of the structure inherent in himself.